2009
DOI: 10.1186/1742-4755-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Audit of short term outcomes of surgical and medical second trimester termination of pregnancy

Abstract: Background: As comparisons of modern medical and surgical second trimester termination of pregnancy (TOP) are limited, and the optimum method of termination is still debated, an audit of second trimester TOP was undertaken, with the objective of comparing the outcomes of modern medical and surgical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This is the first comparative study documenting D&E and medical induction services in a developing country setting, and the first in South Africa, where second trimester abortions are more prevalent than other countries. Despite the different context, our findings on the safety and efficacy of D&E and second trimester medical induction are similar to those reported in more developed country settings [ 4 - 8 , 17 ]. Both D&E and medical induction are being provided safely in this context, although induction frequently required curettage to complete the procedure and had a higher proportion of major immediate complications.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is the first comparative study documenting D&E and medical induction services in a developing country setting, and the first in South Africa, where second trimester abortions are more prevalent than other countries. Despite the different context, our findings on the safety and efficacy of D&E and second trimester medical induction are similar to those reported in more developed country settings [ 4 - 8 , 17 ]. Both D&E and medical induction are being provided safely in this context, although induction frequently required curettage to complete the procedure and had a higher proportion of major immediate complications.…”
Section: Discussionsupporting
confidence: 87%
“…The few studies that have compared medical and surgical second trimester abortion techniques all have been conducted in developed country contexts [ 4 - 8 ]. One small randomized controlled trial (RCT) comparing D&E to the mifepristone regimen at 14-19 weeks' gestation in the United States (U.S.) found that women undergoing medical induction had a higher risk of complications (RR 6.0, 95% CI 0.9-40.3) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unless complications arise, it is midwives, and in particular core midwives, who administer the antiprogesterone and who manage labour and birth during TOP after 20 weeks gestation. Maternal risk factors increase with gestational age and can include postpartum haemorrhage, retained placenta, infection, fever, and even sepsis (Ellis et al, 2010;Gemzell-Danielsson & Lalitkumar, 2008;Mauelshagen, Sadler, Roberts, Harilall, & Farquhar, 2009). In cases of previous caesarean section uterine rupture is a risk factor.…”
Section: Termination Of Pregnancy After 20 Weeks Gestationmentioning
confidence: 99%